Shirk According to Buya Hamka in Al-Azhar Interpretation (Examining the History of Thought and Interpretation) - Sihombing, Muhammad Ebin Rajab (Universitas Ahmad Dahlan, 2023)
There are many verses that talk about shirk and produce quite a variety of interpretations. One of the commentators who is quite detailed in explaining the shirk is Buya Hamka in the interpretation of Al-Azhar. An important aspect of this study apart from looking at how shirk according to Buya Hamka is to examine the history of Buya Hamka's thoughts and interpretations so as to produce a complete interpretation which he put into Tafsir Al-Azhar. This study used a qualitative method of literature review. This method collects data obtained from various sources of literature, books, journal articles, and various related research results. This study found that Shirk according to Buya Hamka was broadly divided into two groups. First, Shirk before Islam, which is included in this category are the perpetrators of major sins and non-Muslims before converting to Islam. Second, Shirk after Islam, which is included in this section is excessive worship of other than Allah and changing God's creation. As for what influenced his thinking and interpretation: 1. Family background, 2. Education, 3. Community organizations, 4. social circumstances. Thus, the results of this study further confirm that the results of thought and interpretation cannot be separated from space and time. Therefore, apart from studying the results of interpretations or interpretation books, it is no less important to study the history of the thoughts and interpretations of a mufassir.